2001
DOI: 10.2514/2.5895
|View full text |Cite
|
Sign up to set email alerts
|

Upper Bounds on the Flight Speed of Hydrocarbon-Fueled Scramjet-Powered Vehicles

Abstract: Estimates of upper bounds on ightMach number for scramjet-powered vehicles operating on liquid hydrocarbon fuels assuming either equilibrium or frozen nozzle chemistry are presented. For an axisymmetric missileshaped vehicle, these upper bounds lie between Mach 9 and 10. Nomenclature A = area C D = drag coef cient C T g = gross engine thrust coef cient C TN = net vehicle force coef cient ER e = effective fuel-air equivalence ratio M = Mach number p = pressure q = dynamic pressure ® = angle of attacḱ c = fuel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…Hydrocarbons are the fuel of choice for low-Mach hypersonic scramjet operations, such as the Air Force HyTech program [13]. Waltrup [14] has shown that a reasonable upper bound on flight Mach number for a hydrocarbon-fueled scramjet is between Mach 9 and 10, which is well within the flight speed range to be examined for practical applications in the near future. Lewis [12] has demonstrated that for a cruiser operating in the Mach 8-10 corridor, in which it is desired to maximize cruise range for a given total takeoff weight, the aerodynamic and volumetric advantages of storable hydrocarbons are about equivalent or superior to the specific impulse advantages of hydrogen in determining cruiser range.…”
Section: Fuelsmentioning
confidence: 98%
“…Hydrocarbons are the fuel of choice for low-Mach hypersonic scramjet operations, such as the Air Force HyTech program [13]. Waltrup [14] has shown that a reasonable upper bound on flight Mach number for a hydrocarbon-fueled scramjet is between Mach 9 and 10, which is well within the flight speed range to be examined for practical applications in the near future. Lewis [12] has demonstrated that for a cruiser operating in the Mach 8-10 corridor, in which it is desired to maximize cruise range for a given total takeoff weight, the aerodynamic and volumetric advantages of storable hydrocarbons are about equivalent or superior to the specific impulse advantages of hydrogen in determining cruiser range.…”
Section: Fuelsmentioning
confidence: 98%
“…However, hydrogen has three to four times a lower energy density than typical storable hydrocarbons, and it is difficult to store and handle on a routine basis. In contrast to hydrogen, hydrocarbon fuels package better, exhibiting a greater energy per unit volume, so that they require less room onboard than hydrogen fuel for an equivalent amount of energy [7]. And now, to model the performance of a dual-mode scramjet engine, the heat release distribution must be accurately predicted, because the heat release distribution have an influence on the thermal choking point, the profiles of pressure and Mach number et al Tomioka et al carried out dual-mode combustion tests with hydrogen fuel injection in diverging section and a one-dimensional calculation to estimate combustion efficiency [8].…”
Section: Introductionmentioning
confidence: 98%
“…In this case, the upper speed limit lies in the range of Mach numbers 1216 [2,3]. There were also studies on hydrocarbon-fuelled scramjets with the upper speed limit on §ight Mach number established in the Mach range of 810 [4]. In either case, the §ow velocity at the entrance of combustor can achieve a Mach number of 45.…”
Section: Introductionmentioning
confidence: 98%